(untitled) (Psychology Travelogs, 2023)
The article provides a theoretical analysis of the concepts of stress resistance, as well as the problem of choosing the optimal strategies for coping with stress by modern women under martial law in Ukraine. It has been established that stress resistance is a dynamic systemic process that ensures the ability of a person to recover, both after negative events, including problems, conflicts and failures, and situations of a positive nature, progress and a state of increased responsibility, ensuring successful adaptation of a person to threats and life problems. The components of personality stress resistance are determined, in particular: cognitive, psychophysiological, emotional-communicative, cognitive, value-volitional. The types of strategies for coping with stress by women in martial law have been clarified: they are focused on solving the problem, focused on regulating emotions and non-adaptive strategies. According to the purpose of the article, an empirical determination of the characteristics of strategies for coping with stress by women was carried out. With the help of the questionnaire, it was found that mostly all respondents in their lives use different types of coping strategies at an average level. Among the respondents, the strategies of “decision planning”, “escape / avoidance” and “confrontation” are most pronounced; the coping strategy “search for social support” is least of all. Using the "Methodology for determining stress resistance and social adaptation" (T. Holmes, R. Rage), we found that a quarter of the women surveyed have a high level of stress resistance and social adaptation, 35% - an average level, 40% - a low level of stress resistance and social adaptation. The data obtained indicate a high probability of occurrence of somatic disorders or diseases in women. The indicators also indicate that women are unable to cope with stress in adaptive ways. Prospects for further scientific research are proposed, which consist in studying the motivational structure of a woman’s personality and the characteristics of their cognitive functions during martial law and developing training programs using art therapy techniques, elements of body-oriented therapy and the group discussion method.